Steady-State Flow Characteristics and End Clearance Optimization of Internal Gear Grease Pump. (28th May 2021) - Li, Xinjian; Tang, Lingfeng; Qian, Ming
Abstract : The internal gear grease pump is a mechanical device used for transfer of high viscosity fluid. The existing clearance between the end faces of the internal or external gear and the floating side plate might cause pump leakage during operation. In order to obtain the optimal end clearance of the internal gear grease pump, the rheological features of the lubricating lithium-based grease for various temperatures are explored via rotating rheometer. Shear force and apparent viscosity are chosen as monitored experimental parameters. The experimental data is fitted to obtain grease rheological features at various temperatures. The end clearance flow field model and the leakage model are established. Fluent software is employed for solving the flow field model and exploring the effect of temperature, end clearance, and speed on grease leakage. Superior grease flow performance is observed with an increase in temperature, which makes it to easier for the grease to leak from the end clearance. With an increase in the end clearance and the working pressure of the pump, an increase in leakage is also observed. Furthermore, it is found that rotational speed also affects the pump leakage. The leakage mechanism is obtained by combining the rheological features of the grease at the end clearance. The mathematical model method is utilized to solve for the optimal value of the end clearance.